TINJAUAN PENDEKATAN SISTEM DALAM MANAJEMEN PENDIDIKAN ISLAM - Eka Widiastuti; Arief Laksono; Romlah; Saiful Anwar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
A systems approach manages educational components in an integrated manner, ensuring the synergy of elements to produce a generation of intelligent and moral Muslims. Even though it is important, its implementation in Indonesia still faces quality challenges, demanding comprehensive improvements for sustainable effectiveness. This research uses a literature review method to collect, analyze and synthesize various literature related to a particular topic. This method summarizes previous research, theories, concepts and findings from various sources such as books, journal articles, research reports and other documents, in order to provide a comprehensive understanding and overview of knowledge relevant to the topic under study. Emphasizes the importance of implementing a systems approach in educational management Islam to improve the quality of education. This approach integrates educational components holistically. Despite adoption, challenges such as quality gaps still exist. Sustainable strategies, Islamic leadership, strengthening infrastructure, technology, and synergy between components are needed to make Islamic education relevant and competitive. The application of a systems approach in Islamic education management must be strengthened with sustainable strategies and leadership based on Islamic values. Strengthening infrastructure, utilizing technology, and increasing synergy between educational components are very important. Focusing on improving the quality of human resources and Islamic organizational culture is necessary so that Islamic education is relevant, adaptive and able to compete in the modern era.